Otimização do armazenamento e geração de energia a biogás visando ao gerenciamento das redes de distribuição - Brignol, Wagner da Silva (2017)
The increasing use of renewable sources of distributed generation (DG) and also the perspective of the use of energy storage systems (ESS) in distribution systems, makes it imperative that distributors adopt measures to help them manage and operate their distribution networks, obtaining a strategic use of these sources, in order to minimize the possible negative impacts resulting from these connections, and guarantee the quality of energy supply to its consumers. In this context, biogas DG meets this evolution, since this type of DG has an integrated biogas energy storage system, called in this thesis (bio Energy Storage System - bioESS), which allows the DG converts the biogas into electrical energy at appropriate times. Thus, this Thesis aims to present the development of a methodology of optimization applied in biogas energy storage systems with the objective of determining multi-level operational regimes distributed generation. In order to do so, we used the integer linear programming (ILP) to propose an objective function (OF) to optimize the use of the stored biogas, using as parameters from the biogas production curve and the load curve of the biogas producing property. The OF restrictions were determined according to the bioESS management operational characteristics, such as: minimum, maximum and initial biogas stock. The operational regime to be achieved by applying the method is based on two proposed models, in which DG prioritizes the use of biogas for total or partial service of the biogas producing property loads and the remaining energy potential is stored for strategic use. As a result of the optimization, a multi-level operational regime for DG is obtained, in which power and the options of periods are indicated in which the energy distributor can be guaranteed to use the energy stored in the bioESS, allowing a strategic management of the dispatch and storage of the energy that can be produced from biogas. This methodology is verified by means of a case study where the data of a rural swine production participant in ANEEL P&D P14 / 2012 are used.